Possibility of Phytotherapeutic Effect on Vegetative and Psychoemotional State of Adolescents with Autonomic Dysfunction Syndrome - N.V. Nagornaya; K.V. Belomerya; I.Yu. Muravskaya; Ye.V. Bordyugova (Zaslavsky O.Yu., 2014)
The article presents the results of a study on clinical efficacy and safety of using complex herbal preparation Sedafiton® in schoolchildren aged 15-18 years with autonomic dysfunction syndrome. A positive effect of the drug on the well-being of children, autonomic tone, blood pressure and heart rate, level of anxiety was revealed. Clinical significance was noted after 14 days of phytotherapy with further its increase up to completion of 30-day course and preservation for 60 days in more than a half of the children, indicating pronounced and persistent vegetative stabilizing, sedative and anxiolytic effect. The drug was well tolerated, had no side effects, signs of addiction and withdrawal syndrome.